Design of bacterial dna microarray for pathogen detection of acinetobacter baumannii, pseudomonas aeruginosa and staphylococcus aureus - Teo, Zhi Liang. (2010)
Pathogen detection is of growing importance amongst the various DNA microarray applications emerging, particularly given the ability of microarrays to deliver rapid and accurate results for clinical detection. Nosocomial bacteria are clinically significant due to their prevalence in hospital infections and increasing antimicrobial resistance which complicates treatment. Furthermore, effective treatment is often delayed by the slow culture-based detection methods currently in use which can be compromised by misdiagnoses. While advantageous for clinical detection, commercial DNA microarrays often limit analysis to generic purposes such as gene expression studies for a few selected model organisms. Consequently, there is a need for custom microarray design, and the present project was approached to design microarray probes for clinical detection of A. baumannii, P. aeruginosa and S. aureus which are the most common nosocomial bacteria in hospitals.